Von-Data Hybrid System Architecture - Shaout, Adnan; A. Nsour, Atif (Malaysian Journal of Computer Science, 2003)
In this paper a computing system has been proposed which involves both the principles and the approaches of data flow and Von-Neumann systems. The proposed model incorporates several new features like having a dedicated graphical processor, error correcting algorithms embedded in a systolic array and limiting the addressing mode to improve the execution speed. The proposed architecture can also function as a static and dynamic machine.